An injected quantity estimation technique based on time–frequency analysis. (November 2021) - Ferrari, Alessandro; Jin, Zhiru; Vento, Oscar; Zhang, Tantan
Abstract: An innovative injected quantity estimation method, based on time–frequency​ analysis, has been developed for passenger car Common-Rail (CR) injection systems. This method involves capturing the pressure time history from a transducer installed along the rail-to-injector pipe, and its overall accuracy has been found to be within 1.5 mg. The dependence of the injected mass on the fuel temperature has been investigated, and the correlation of the injected mass with the nominal rail pressure and the energizing time has been evaluated for different thermal regimes. It has been verified that if the duration of the hydraulic injection is considered instead of the energizing time, the influence of the temperature on the injected mass is implicitly taken into account. Thus, the corresponding correlations between the injected mass and the duration of the hydraulic injection have been obtained for different nominal rail pressures. The duration of the hydraulic injection has been measured through an effective time–frequency analysis technique, which has been used to realize a virtual sensor of the needle lift. The experimental campaign has been performed over a wide range of working conditions for single injections, and the accuracy of the innovative prediction methodology, which can be exploited to design a closed-loop control of the injected mass, has been assessed. Highlights: A correlation between the injection temporal length and injected mass is obtained. Nozzle opening and closure are detected by means of a virtual needle-lift sensor. The injected mass is predicted from a pressure trace measured at the injector inlet.